ANALISIS PENINGKATAN KESEJAHTERAAN PEDAGANG PASAR NGARSOPURO SESUDAH PENATAAN - Suprihatmi Sri Wardiningsih, Retno Susanti & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT The main purpose of this research is to determine the significance of differences in prosperity Solo Ngarsopuro market traders after the market arrangement depend on the factor market place, value added merchandise and market reach or market share. The results of the data analysis using SPSS Release 12 is obtained: (1) From the questionnaire test of each variable, showed that all instruments research are valid and reliable at the 0.05 level. (2) The results of the analysis of the data shows the market place t value 46,699 > t table 1,96, t value merchandise 461,424 > t table 1,96, t value market reach 47,153 > t table 1,96, and t value prosperity 57,937 > t table 1,96. Thus, the hypothesis that state there is an increase in the prosperity of traders after the market arrangement, depend on the location factor, value added merchandise and market reach is attested. Keywords: tradesman welfare, market Ngarsopuro, configuration market.